Health information sources for different types of information used by Chinese patients with cancer and their family caregivers. (7th September 2016) - Xie, Bo; Su, Zhaohui; Liu, Yihao; Wang, Mo; Zhang, Ming
Abstract: Context: Little is known about the information sources of Chinese patients with cancer and their family caregivers, yet this knowledge is critical for providing patient‐centred care. Objective: To assess and compare the information sources used by Chinese patients with cancer and their family caregivers. Design: The validated Health Information Wants Questionnaire (HIWQ) was translated and administered in March 2014. Setting: The oncology department of a general hospital in south‐west China. Participants: A convenience sample of 198 individuals, including 79 patients with cancer (mean age=55.24, SD=13.80) and 119 family caregivers (mean age=46.83, SD=14.61). Main outcome measures: Ratings on the HIWQ items assessing information sources for different types of information. Results: The interaction between information source and group was significant ( F 3, 576 =6.32, P <.01). Caregivers obtained more information than patients from the Internet. Caregivers and patients did not differ in the amount of information they obtained from doctors/nurses, interpersonal contacts or mass media. The interaction between information type and information source was significant ( F 18, 3456 =6.38, P <.01). Participants obtained more information of all types from doctors/nurses than from the other three sources and obtained more information from interpersonal contacts than from mass media or the Internet. Conclusions: The information sources of Chinese patients with cancer and their family caregivers were similar, with an important difference that caregivers obtained more online information than patients. These findings have important implications for patient care and education in China where the family typically plays a major role in the care and decision making.